Influence of the Crc regulator on the hierarchical use of carbon sources from a complete medium in Pseudomonas. (18th January 2016) - La Rosa, Ruggero; Behrends, Volker; Williams, Huw D.; Bundy, Jacob G.; Rojo, Fernando
Summary: The Crc protein, together with the Hfq protein, participates in catabolite repression in pseudomonads, helping to coordinate metabolism. Little is known about how Crc affects the hierarchy of metabolite assimilation from complex mixtures. Using proton Nuclear Magnetic Resonance (NMR) spectroscopy, we carried out comprehensive metabolite profiling of culture supernatants (metabolic footprinting) over the course of growth of both P seudomonas putida and P .  aeruginosa, and compared the wild‐type strains with deletion mutants for crc . A complex metabolite consumption hierarchy was observed, which was broadly similar between the two species, although with some important differences, for example in sugar utilization. The order of metabolite utilization changed upon inactivation of the crc gene, but even in the Crc‐null strains some compounds were completely consumed before late metabolites were taken up. This suggests the presence of additional regulatory elements that determine the time and order of consumption of compounds. Unexpectedly, the loss of Crc led both species to excrete acetate and pyruvate as a result of unbalanced growth during exponential phase, compounds that were later consumed in stationary phase. This loss of carbon during growth helps to explain the contribution of the Crc/Hfq regulatory system to evolutionary fitness of pseudomonads.